The Effect of Polyacrylamide as Stabilization Material on Bearing Capacity of Subgrade and Unit Price of Work - Ery Radya Juarti; Ruth Esther Ambat; Iskandar; Ahmad Solih; Salma Oktavania; Anissa Puspa Nugraha; Abdallh Lhwaint (Potensi: Jurnal Sipil Politeknik, 2024)
Stabilization is the mixing of soil with other materials, one of which is polyacrylamide (PAM) synthetic polymer. Subgrade stabilization was carried out on local soil at Jalan Cisasawi, Desa Cihanjuang with the percentage of PAM addition of 4%, 6%, 8%, 10%, and 12% of soil weight. This is done to get a high CBR value. In laboratory tests, PAM was shown to increase the bearing capacity of the soil to the optimum at 8% PAM content from dry weight. At 10% and 12% PAM percentages, the soil experienced a decrease in bearing capacity because it was no longer able to accept other substances from outside. CBR testing with 8% PAM content resulted in a soaked CBR value of 16.4% and an unsoaked CBR of 20.5%. In the Free Compressive Strength test with 4% PAM content, PAM can increase the compressive strength value by 162%, 6% PAM by 207% and 8% PAM by 226% of the original soil compressive strength. It was also calculated the unit price of mixing PAM with soil per 1 m3 as a reference for making a cost budget plan, it was proven that the unit price increased as the percentage of PAM increased.